Titanium nanotubes activate genes related to bone formation in vitro - Alfonso Pozio; Annalisa Palmieri; Ambra Girardi; Francesca Cura; Francesco Carinci (Wolters Kluwer Medknow Publications, 2012)
Background: Titanium is used worldwide to make osseointegrable devices, thanks to its favorable characteristics as mechanical proprieties and biocompatibility, demonstrated by in vivo studies with animal models and clinical trials over a forty-year period. However, the exact genetic effect of the titanium layer on cells is still not well characterized. Materials and Methods: To investigate how titanium nanotubes stimulate osteoblasts differentiation and proliferation, some osteoblast genes (SP7, RUNX2, COL3A1, COL1A1, ALPL, SPP1 and FOSL1) were analyzed by quantitative Real Time RT- PCR. Results: After 15 days, osteoblasts cultivated on titanium naotube showed the up-regulation of bone related genes SP7, ENG, FOSL1 and SPP1 and the down-regulation of RUNX2, COL3A1, COL1A1, and ALPL. After 30 days of treatment, the bone related genes SP7, ENG, FOSL1 and RUNX2 were up-regulated while COL3A1, COL1A1, ALPL and SPP1 were down-regulated. Conclusions: Our results, demonstrates that titanium nanotubes can lead to osteoblast differentiation and extracellular matrix deposition and mineralization in dental pulp stem cells by the activation of osteoblast related genes SPP1, FOSL1 and RUNX2.